2001
DOI: 10.1159/000050561
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydrofluoroalkane-Beclomethasone Dipropionate Autohaler<sup>TM</sup> with Budesonide Turbuhaler<sup>TM</sup> in Asthma Control

Abstract: Background: Hydrofluoroalkane-beclomethasone dipropionate AutohalerTM (HFA-BDP AH) is a breath-actuated chlorofluorocarbon (CFC)-free metered dose inhaler in which BDP is in a solution of HFA propellant. Budesonide TurbuhalerTM (BUD TH) is a breath-dependent dry powder inhaler. Objectives: To test the hypothesis that half the daily dose of HFA-BDP AH would provide an equivalent control of asthma symptoms to the BUD TH. Methods: This was an 8-week open study in patients with symptomatic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…6,7 Even when assuming that Table I. Data shown are averages 6 SEMs; significant changes from DPI-BUD: *P < .05; P < .01. the use of each device is optimal in study populations that are being compared, the equivalence factor for dosing between any 2 formulations will depend on the study parameter used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Even when assuming that Table I. Data shown are averages 6 SEMs; significant changes from DPI-BUD: *P < .05; P < .01. the use of each device is optimal in study populations that are being compared, the equivalence factor for dosing between any 2 formulations will depend on the study parameter used.…”
Section: Discussionmentioning
confidence: 99%
“…4 Scintigraphy studies have demonstrated more than 50% lung deposition of HFA-BDP aerosols in healthy volunteers and in patients with asthma 3-5 with a preferential distribution toward peripheral air spaces. 5 Comparative clinical studies using spirometric indices have indicated that only half the HFA-BDP dose suffices to obtain similar or better therapeutic efficacy than the standard inhaled steroids [6][7][8][9][10][11][12] with no clinically relevant systemic side effects for daily HFA-BDP doses below 800 mg. 13 Several studies have attempted to assess the effect of HFA-BDP on small airway function. 6,10,[14][15][16][17] Improvements in end-expiratory flows were observed when HFA-BDP was added to the baseline steroid treatment of patients with poorly controlled asthma, 14 or when steroid-naive patients with asthma were given HFA-BDP.…”
mentioning
confidence: 99%
“…One possibility could be that the increased and more peripheral lung deposition from Autohaler was not associated with a similar increase in clinical effect. This seems unlikely, since several studies in children and adults using other outcomes have found increased clinical effects from Autohaler, as compared with less effective delivery devices [25][26][27][28][29]. Another reason could be that BDP is not suitable for q.d.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do require a sufficient peak inspiratory flow rate (PIF) to achieve an adequate concentration of small respirable particles of the drug to achieve optimal lung deposition [4,5,6]. In contrast, HFA-BDP provides a pressurized metered dose of a micro aerosol, which results in a smaller particle size than with conventional DPIs; thus, it is expected to deposit drug particles into the smaller airways of the lung over a wider range of PIFs [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…The handheld In-Check device (Clement Clarke, Harlow, UK) has recently become available for measuring the PIF and is reportedly useful in assessing whether children and adults should use a DPI [4,5,6,7,8,9,10,11]. It has also been reported that 12% of adult patients with asthma or chronic obstructive pulmonary disease are unable to generatethe optimal inspiratory flow required for DPI use [12].…”
Section: Introductionmentioning
confidence: 99%